TRACE OF THE ADJACENCY MATRIX n×n OF THE CYCLE GRAPH TO THE POWER OF TWO TO FIVE - Aryani, Fitri; Puspita, Dian Ayu; Marzuki, Corry Corazon; Muda, Yuslenita (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
The main aim of this research is to find the formula of the trace of adjacency matrix from a cycle graph to the power of two to five. To obtain the general form, the first step is finding the general formula of the adjacency matrix from a cycle graph to the power of two to five. Furthermore, the formula of the trace of adjacency matrix which is mentioned above obtained and proven by direct proof. We also present an implementation of the formula which is given by an example.